ANALISIS KOMUNIKASI ANTAR BUDAYA DALAM RITUAL KEDURAI AGUNG DI DESA TABA TEMBILANG KECAMATAN ARGAMAKMUR BENGKULU UTARA - Yupita Adria; Sapta Sari; Yanto Yanto (UNIVED PRESS, Universitas Dehasen Bengkulu, 2018)
This study aims to determine the intercultural communication in Kedurai Agung ritual atTaba Tembilang Village Argamakmur District North Bengkulu. The data collection method used is observation, interview, and documentation. The theory used in this study is the theory according to Deddy Mulyana about intercultural communication that has a personal function and social function. Social function consists of social identity, declaring social integration, and adding knowledge. Social function consists of supervisory function, bridging function, socialization and entertaining.The results showed that intercultural communication express social identity can be viewed from the origin of tribes, religions, and different cultures. Social integration accepts the differences between each of the existing tribes, and appreciates each other in spite of different tribes. Adding knowledge to each other learns the values of culture in Kedurai Agung ritual.The social function of supervision supervises each other. Different cultures are a bridge over the differences to unite hospitalitywith people of different tribes and cultures. To socialize the cultural values in this village is very good because they realize the important of study the existing cultures. Intercultural entertainment is clearly visible from the information obtained because Kedurai Agung ritual held in Taba Tembilang village is held only once a year and although many different tribes have a sense of caring and mutual respect for others.